Cerebral oxygenation during changes in vascular resistance and flow in patients on cardiopulmonary bypass – a physiological proof of concept study. (17th October 2016) - Sperna Weiland, N. H.; Brevoord, D.; Jöbsis, D. A.; de Beaumont, E. M. F. H.; Evers, V.; Preckel, B.; Hollmann, M. W.; van Dieren, S.; de Mol, B. A. J. M.; Immink, R. V.
Summary: Despite a rise in blood pressure, cerebral oxygenation decreases following phenylephrine administration, and we hypothesised that phenylephrine reduces cerebral oxygenation by activating cerebral α1 receptors. We studied patients on cardiopulmonary bypass during constant flow. Phenylephrine raised mean arterial pressure (α1 ‐mediated) from mean (SD) 69 (8) mmHg to 79 (8) mmHg; p = 0.001, and vasopressin raised mean arterial pressure (V1 mediated) from 69 (8) mmHg to 83 (6) mmHg; p = 0.001. Both drugs elicited a comparable decrease in cerebral oxygenation from 61 (7)% to 60 (7)%; p = 0.023 and 61 (8)% to 59 (8)%; p = 0.022, respectively. This implies that after phenylephrine or vasopressin administration, cerebral oxygenation declines as a result of cerebral vasoconstriction, due to either both cerebral α1 and V1 receptors being equipotentially activated or to an intrinsic myogenic mechanism of cerebral vasculature in reaction to blood pressure elevation.